MARKETING COMMUNICATION STRATEGY OF SOLO RADIO FM IN EFFORTS TO INCREASE THE NUMBER OF ADVERTISERS - Melania Tri Kartika; Joko Sutarso (Jurnal Visi Komunikasi, 2026)
Amid the acceleration of media digitalization, local radio continues to hold a strategic position as a marketing communication medium, particularly for locally based advertisers. Nevertheless, empirical studies that comprehensively examine local radio marketing communication strategies through the integration of pull, push, and pass approaches remain limited. This study aims to analyze the marketing communication strategy of Solo Radio FM in increasing the number of advertisers by using the perspective of Social Exchange Theory. The research employs a descriptive qualitative approach, with data collected through in-depth interviews and observation. Data analysis was conducted using content analysis. The findings indicate that improvements in broadcast program quality and listener loyalty function as the main attractions for advertisers through a pull strategy. Personal communication approaches and flexibility in advertising packages strengthen the negotiation process within the push strategy. Meanwhile, the maintenance of long-term relationships based on trust and the provision of added value supports the sustainability of cooperation through the pass strategy. These results confirm that relationally oriented and adaptive marketing communication strategies play an important role in sustaining the business of local radio stations.